Determinação da constante do produto de solubilidade do acetato mercuroso, com a variação da força iônica, em meio aquoso - De Moraes, Mercedes [UNESP]; Pezza, Leonardo [UNESP]; Melios, Cristo Bladimiros [UNESP]; Molina, Manuel; Pezza, Helena Redigolo [UNESP]; Peres, Adriana Martins [UNESP]; Villafranca, Ana Cristina [UNESP]; Carloni Filho, João [UNESP] (My University, 1996)
The conditionals (Kps) and thermodynamics (Kops ) solubility products of mercurous acetate have been determined, in aqueous solution, at 25°C and ionic strength (I) comprised between 0.300 and 3.000 mol/L (NaClO4). The investigation was earned out potentiometrically by using a second class electrodes which responds to acetate ions. The values obtained for [pKps (I)] were: 9.49±0.08 (0.000); 9.51±0.08 (0.300); 9.53±0.08 (0.500); 9.54±0.08 (0.700); 9.55±0.09 (0.900); 9.57±0.09 (1.200); 9.59±0.10 (1.500); 9.61±0.10 (1.800); 9.63±0.10 (2.100); 9.65±0.11 (2.400); 9.67±0.11 (2.700) e 9.69±0.12 (3.000).
Determination of solubility product of mercurous acetate at various ionic strengths in aqueous medium
Keywords: Acetate second class electrodes; Ionic strength; Mercurous acetate; Potentiometry; Solubility products